Scale dependence of ecological assembly rules: Insights from empirical datasets and joint species distribution modelling. (23rd June 2020) - Mod, Heidi K.; Chevalier, Mathieu; Luoto, Miska; Guisan, Antoine
Abstract: A comprehensive understanding of the scale dependency of environmental filtering and biotic interactions influencing the local assembly of species is paramount to derive realistic forecasts of the future of biodiversity and efficiently manage ecological communities. A classical assumption is that environmental filters are more prevalent at coarser scales with diminishing effects towards the finest scales where biotic interactions become more decisive. Recently, a refinement was proposed stipulating that the scale dependency of biotic interactions should relate to the type of interaction. Specifically, the effect of negative interactions (e.g. competition) should diminish with coarsening scale, whereas positive interactions (i.e. facilitation) should be detected irrespective of the scale. We use multiple vascular plant species datasets sampled at nested spatial scales (plot size varying from 0.04 to 64 m 2 ) and recently developed joint species distribution models to test the hypotheses. Our analyses indicate slightly stronger environmental filtering with increasing plot size. While the overall strength of biotic interactions did not vary consistently across scales, we found a tendency for negative interactions to fade away with increasing plot size slightly more than positive interactions. Synthesis . We provide partial, but not unambiguous, evidence of the scale dependency of ecological assembly rules. However, our correlative methodology only allows us to interpret the findings as indication of environmental filtering and biotic interactions. Abstract : We provide partial, but not unambiguous, evidence of the scale dependency of ecological assembly rules. However, our correlative methodology only allows us to interpret the findings as indication of environmental filtering and biotic interactions.